Cranial polyneuropathy caused by vertebrobasilar dolichoectasia. - Poh Sen, Tay; Mat Daud, Noor Aida; Hashim, Hilwati (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Vertebrobasilar Dolichoectasia (VBD) is a condition characterized by abnormal elongation, dilatation and tortuosity of the vertebrobasilar system. It is usually asymptomatic but rarely, it can present with cranial nerve compression symptoms. We present a case of simultaneous trigeminal neuralgia and hypoglossal nerve palsy due to compression by VBD. Neuroimaging plays an important role in diagnosing this condition so that further treatment can be provided.